Solitons and the new renewable energy approach - Mahmoud Akdi; Moulay Brahim Sedra (Renewable Energy and Sustainable Development, 2015)
This article aims at deepening research on the new renewable energy production from the dams reservoir. Coupled to the solitary waves, the wind generated waves present an attractive natural phenomenon that deserves to be emphasized. The Adomain numerical method is used to model the practical observation regarding the soliton propagation. The concrete cases contained in this document provide an illustration of the given principals.